The Depiction of Tolerance in Sufi Sources - Rajabova Rohila Zakirovna (Indonesian Culture and Religion Issues, 2025)
This study explores the concept of tolerance in Sufi sources, particularly within the Naqshbandiya tariqah, and its impact on interfaith harmony and social coexistence. The research aims to analyze the historical and philosophical foundations of tolerance in Sufism and its role in fostering justice, equality, and mutual respect among different religious and ethnic groups. The study employs a qualitative descriptive method, utilizing literary analysis and historical interpretation of Sufi manuscripts, the Qur’an, and Hadith. Primary sources include classical Sufi texts and scholarly works from the Manghit period, which emphasize the significance of tolerance and community-oriented teachings in Sufi thought. The findings reveal that Sufi teachings strongly advocate for tolerance as a fundamental principle of justice, rooted in Islamic teachings and reflected in the practices of Sufi orders. The Naqshbandiya-Mujaddidiya tariqah, in particular, promotes an active social life alongside spiritual discipline, reinforcing social unity and ethical conduct. The study underscores that Sufi principles continue to play a crucial role in contemporary discussions on interfaith harmony and cultural integration, highlighting their relevance in addressing modern religious and social challenges